Sociological stalking? Methods, ethics and power in longitudinal criminological research - Sharpe, Gilly (Criminology & criminal justice, 2017)
Scholarship on criminal careers and desistance from crime employing longitudinal methodologies has paid scant attention to sociological and anthropological debates regarding epistemology, reflexivity and researcher positionality. This is surprising in light of a recent phenomenological turn in desistance research wherein (former) lawbreakers’ identity, reflexivity and self-understanding have become central preoccupations. In this article I interrogate aspects of the methodological ‘underside’ of qualitative longitudinal research with criminalized women through an examination of the surveillant position of the researcher. Focusing on methods, ethics and power, I examine some contradictions of feminist concerns to ‘give women voice’ in research involving re-tracing an over-surveilled and highly stigmatized population. I reflect on the effects of researcher positionality through a conceptualization of re-tracing methods as, at worst, a form of sociological stalking.